Analysis of ERBB4 Variants in Amyotrophic Lateral Sclerosis Within a Chinese Cohort - Wang, Fan; Liu, Xiangyi; He, Ji; Zhang, Nan; Chen, Lu; Tang, Lu; Fan, Dongsheng (Frontiers in Neurology, 2022)
ERBB4 is related to amyotrophic lateral sclerosis (ALS) in patients with a family history and is thought to cause ALS-19. We screened 448 ALS patients, including 364 sporadic ALS (sALS) and 84 familial ALS (fALS) patients with ERBB4 variants, in a Chinese cohort. In total, 12 missense variants were identified in this study. Of these, 3 (p.Arg106His, p.Gln164Pro, and p.Val212Leu) were absent from the in-house healthy control cohort and population databases and predicted to be likely pathogenic. Genetic burden analysis did not reveal an increase in damaging variants of the ERBB4 gene. We considered that most of the missense variants in ERBB4 were not pathogenic, but certain variants, such as p.Arg106His, p.Gln164Pro, and p.Val212Leu, were likely pathogenic. The phenotype of these three patients carrying ERBB4 variants revealed the typical clinical manifestations of ALS without cognitive dysfunction. We concluded that ERBB4 likely pathogenic variants account for ~0.67% of ALS patients in China. It is necessary to interpret the relationship between the disease and variants carefully for ALS patients with ERBB4 gene variants.